Diseño y evaluación de arquitecturas de computadoras : Marta Bertrán Pardo y Antonio Guzmán Sacristán, Pearson Educación, Madrid, 2010 - Villagarcía Wanza, Horacio A. (2011)
In the first paragraph of the Introduction of the book the authors say "The definition of computer architecture has generated many discussions since the emergence of what could be considered the first computer in 1943, the ENIAC". Later they add "The main idea of all the proposals made in this direction is the same: define of computer components in different levels of study to produce a hierarchical description and to facilitate their understanding and design”. The authors' goal is to provide a textbook (written in Spanish) that systematically collect the most important techniques of design and evaluation of computer architectures.